TWIST SETTING TEMPERATURE AND TIME EFFECTS ON MORPHOLOGY OF POLYETHYLENE TEREPHTHALATE YARN - Yildirim, Kenan; Kostem, A. Melek; Aydin, Nurcan; Tuna, Huseyin; Cenan, Ayhan (Ege Univ, 2014)
The twist on the yarn should be fixed by heat to remove twist liveliness. This procedure changes the properties of polyethylene terephthalate (PET) yarn in aspect to both fiber morphology and yarn mechanical behavior. The yarn properties are affected by heat setting process factors which mainly are heat-setting method, temperature and time. This study investigates the effect of temperature and time of the heat setting processes on the yarn properties. The change of the morphology of the yarn was determined by tensile test, differential scanning calorimetric (DSC) analysis, boiling water shrinkage test, bobbin hardness and twist amount per unit length test. The study demonstrates that the time of the heat setting does not have a considerable effect on the PET yarn properties. The temperature of the heat setting has dominant influence onto the properties of the PET yarn, especially on the boiling water shrinkage and tensile behavior. The tensile strain and bobbin hardness increase, and shrinkage decrease with increasing heat setting temperature. The force-strain curve shape is changed by altering twist setting parameters. These results show us that heat setting temperature related to stress relaxation arise from twist insertion, rearrangement of the macromolecules and molecular orientation in the amorphous region.
Keywords: Heat setting; Twist fixation; PET filament; Structure-property relationships